A qualitative and quantitative comparison of adverse drug reaction data of anti-epileptic drugs in various sources of drug information - Kullar, Keerat Kaur; Kaur, Prabhsimran; Singh, Aanandita; Randhawa, Gurpreet Kaur (International Journal of Basic & Clinical Pharmacology, 2020)
Background: It is essential to spread awareness about known adverse drug reactions (ADRs) for identification, prevention and their proper management. The aim of this study is to assess disparities in documented ADRS of antiepileptic drugs in various sources of drug information. Methods: An observational, cross sectional study was done to compare different drug information sources for ADRs. Six sources of information namely: National Formulary India (2011), Drug Today (2018), Current index of medical specialties (CIMS), and some textbooks like Lippincott’s illustrated reviews: Pharmacology (2012), Brenner and Stevens’ Pharmacology (2018) and George and Goodman and Gilman’s (GG): The pharmacological basis of therapeutics (2018) were critically analysed for ADRs of a total of 34 drugs. Prototype drugs and most commonly prescribed antiepileptic drugs, were chosen for study. They were categorized according to therapeutic classification and guidelines by Indian Society of Epilepsy. ADRs were categorized according to various body systems, and serious and life threatening ADRs, then were tabulated and compared. Qualitative and quantitative analysis of this data was also done. Results: None of analysed sources mentioned all antiepileptic drugs. GG contained information for maximum number of drugs studied (76.4%) and National Formulary of India gave information for (52.9%) drugs only. There was wide variability among various resources while listing ADRs. CIMS listed maximum number of ADRs (85.5%) while minimum was included in Brenner and Stevens’ Pharmacology (13%) for all antiepileptic drugs. The quality of data though limited was relatively better in CIMS, but none of sources studied were found to be complete. Conclusions: No source of information provided complete information about adverse effects of all 34 anti-epileptic drugs. Academicians and policymakers can work towards providing complete ADR information in all sources of information and updating it from time to time. Thus, making drug use safer in patients of epilepsy.